2012
DOI: 10.1371/journal.pone.0029343
|View full text |Cite
|
Sign up to set email alerts
|

CART Peptide Is a Potential Endogenous Antioxidant and Preferentially Localized in Mitochondria

Abstract: The multifunctional neuropeptide Cocaine and Amphetamine Regulated Transcript (CART) is secreted from hypothalamus, pituitary, adrenal gland and pancreas. It also can be found in circulatory system. This feature suggests a general role for CART in different cells. In the present study, we demonstrate that CART protects mitochondrial DNA (mtDNA), cellular proteins and lipids against the oxidative action of hydrogen peroxide, a widely used oxidant. Using cis-parinaric acid as a sensitive reporting probe for pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 74 publications
(121 reference statements)
5
47
0
Order By: Relevance
“…The peptide encoded by the cocaine and amphetamine regulated transcript (CART) is upregulated by psychostimulants, and was shown to localize in mitochondria and to have antioxidant effects (Mao, Meshul, Thuillier, Goldberg, & Reddy, 2012). Thus, cocaine may also have some indirect effects on mitochondria through upregulation of CART, which was shown to interact with succinate dehydrogenase subunit B, stimulating its activity and increasing ATP production (Mao et al, 2007).…”
Section: Cocaine and Brain Mitochondria Chapter | 21 213mentioning
confidence: 99%
“…The peptide encoded by the cocaine and amphetamine regulated transcript (CART) is upregulated by psychostimulants, and was shown to localize in mitochondria and to have antioxidant effects (Mao, Meshul, Thuillier, Goldberg, & Reddy, 2012). Thus, cocaine may also have some indirect effects on mitochondria through upregulation of CART, which was shown to interact with succinate dehydrogenase subunit B, stimulating its activity and increasing ATP production (Mao et al, 2007).…”
Section: Cocaine and Brain Mitochondria Chapter | 21 213mentioning
confidence: 99%
“…The nanoparticle exposure leads to impairments in normal neurons [20,21], microglia [22] and even aggravate the process of brain pathology was reported earlier [5]. Ion channels serve a subtle indicator of the condition and viability of the cells.…”
Section: Introductionmentioning
confidence: 80%
“…by modulation of the current reading to alterations in functionality [23]. Previous studies revealed that the nanoparticles can impair cell function and even induce certain cell death [20]. Exposure of metallic nanoparticles such as Ag in a neuroendocrine cell line (PC-12 cells) induces neurotoxicity, characterized by the reduction in the level of DA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that CART has a general cytoprotection in mammalian and human cells [12]. Using cis-parinaric acid as a sensitive reporting probe for peroxidation in membranes, and a lipid-soluble azo initiator of peroxyl radicals, we found that CART has an antioxidant property.…”
Section: Cart Has a Neurotrophic Role Via Mitochondria And Antioxidanmentioning
confidence: 93%
“…CART is one of the latest hormones, expressed in the nervous system and circulatory system with multiple functions. We recently found that CART is a mitochondrial booster and a novel endogenous antioxidant [11,12], suggesting its potential relationship with neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%